A comprehensive and critical review on recent progress in anode catalyst for methanol oxidation reaction. Issue 1 (2nd January 2022) - Yuda, Afdhal; Ashok, Anchu; Kumar, Anand
ABSTRACT: The synthesis of anode electrocatalyst with high activity and durability for methanol oxidation reaction has been one of the main focuses of researchers in recent years. Several works are reviewed in this paper to summarize and compare the performance of electrocatalysts comprising of noble and non-noble metals. The effect of manipulating catalysts by introducing nanostructured morphology, metal alloys, support materials, acidic or basic electrolyte, and synthesis methods are also examined. The paper finally concludes with details of challenges that are generally faced in making direct methanol fuel cell (DMFC) a reliable source of energy for future prospects, and the approach to be taken to reduce the complexity in synthesizing new generations of anode electrocatalysts.